Land use/cover predictions incorporating ecological security for the Yangtze River Delta region, China. (December 2020) - Zhang, Dou; Wang, Xiangrong; Qu, Liping; Li, Shicheng; Lin, Yuanping; Yao, Rui; Zhou, Xiao; Li, Jingye
Graphical abstract: Highlights: Rapid changes in anthropogenic land use threaten ecological security. A land use/cover prediction framework embedded with ecological security was developed. Habitat quality, ecosystem services, and landscape connectivity were considered. Ecological security source areas in Yangtze River Delta (YRD) were identified. Land use/cover in YRD for 2030 were predicted via FLUS model. Abstract: Rapid changes in anthropogenic land use threaten ecological security; thus, it is vital to determine future land use structures and spatial layouts for ecological security and sustainable development. Studies on scenario-based land use simulations have taken insufficient account of land use in terms of ecological security and this prevented the realization of ecological civilization. Therefore, in this study, we developed a land use/cover prediction framework that incorporates ecological security. Focusing on ecological security objectives, we integrated habitat quality, the importance of ecosystem services and landscape connectivity to identify the ecological security source areas (ESSA) as a minimum protection area in the Yangtze River Delta (YRD) region. We then set up ESSA-based ecological protection (EP) and natural growth (NG) scenarios to predict land use/cover in the YRD region for 2030 using the future land use simulation (FLUS) model. The results show that the total area of the ESSA is 64, 911 km 2, accounting for 32.51% of the YRD, mainly in southern Anhui and western Zhejiang provinces. Under the NG scenario, construction land shows the highest growth proportion by 2.10% of the total area of YRD, while the farmland area decreases by 1.73%, followed by woodland (0.27%). Under ESSA-based EP, the areas of woodland and construction land increase by 1.11% and 0.7%, respectively. Through the delineation of ESSA, 159 km 2 of woodland, 150 km 2 of orchard, 523 km 2 of water area and 98 km 2 of wetland are protected; in addition, the growth of the construction land slows down and all new construction land is located outside the ESSA under ESSA-based EP. The findings of this study can provide fundamental scientific guidance for land spatial planning given an ecological security premise.